Implementation of Cooperative Learning Method in Improving Civic Education Learning Outcomes of Third Grade Students - Binti Sulyani; Habiburrahman Rizapoor (GENIUS: Journal of Elementary Pedagogy and Innovation Studies, 2026)
Civic education learning in Madrasah Ibtidaiyah requires methods that encourage student activity and cooperation in order to improve learning outcomes. This study aims to describe the planning, implementation, and evaluation of the Cooperative Learning method in improving the civic education learning outcomes of third-grade students at MI PSM 1 Baron. This study uses a qualitative approach with a descriptive research type. The research subjects were third-grade teachers, with secondary data sources in the form of school documentation and archives. Data collection techniques included observation, interviews, and documentation. The data were analyzed deductively and comparatively. The results showed that the learning plan was systematically prepared in accordance with the objectives and characteristics of the students. The implementation of the Cooperative Learning method was able to increase student activity, cooperation, and understanding. The learning evaluation showed an increase in student learning outcomes. Thus, the Cooperative Learning method is effective when applied in Civic Education learning at Madrasah Ibtidaiyah.